Double Burden of Persons with Disabilities: Are Those More Likely to Suffer from Chronic Disease? - Kusumawardani, Salsabila; Puspitasari, Hardiyani; Danuza, Muhammad Ciro; Martak, Yusuf Faisal (UI Scholars Hub, 2024)
This study examines the likelihood of persons with disabilities experiencing chronic diseases compared to those without disabilities, emphasizing the role of demographic characteristics. Prior research shows that individuals with disabilities have a higher risk of chronic diseases due to pre-existing health conditions, secondary complications, healthcare access barriers, and limited health education. Beyond these factors, we argue that demographic characteristics—such as age, gender, insurance status, and living environment—also shape daily habits and lifestyles that influence long-term health outcomes. Using probit regression analysis, this study quantifies the probability of chronic disease among persons with disabilities. Our findings indicate that individuals with disabilities who are female, uninsured, unhappy, reside in urban areas, are of productive age, and live in larger households face a higher likelihood of chronic diseases. Compared to their rural and non-productive-age counterparts, they may encounter more significant stressors, unhealthy lifestyle patterns, and limited preventive healthcare. These results highlight the need for targeted health interventions that address both structural and demographic factors to reduce chronic disease risks among persons with disabilities.